Carbon doping - A key for the substitute of thoriated tungsten. (August 2018) - Traxler, H.; Wesemann, I.; Knabl, W.; Nilius, M.; Morkel, M.; Höbing, T.; Mentel, J.; Awakowicz, P.
Highlights: The Bochum Modell Lamp provides a highly instrumented insight to processes in short arc lamps, e.g. flickering. Carbon doping of lanthanated cathode material improves the light output stability of short arc lamps. Carbon doping activates bulk diffusion of Lanthanum in Tungsten based material.